Tribology in materials and manufacturing wear, friction and lubrication - Patnaik, Amar; Kukshal, Vikas (IntechOpen, 2021)
Tribology in Materials and Manufacturing - Wear, Friction and Lubrication brings an interdisciplinary perspective to accomplish a more detailed understanding of tribological assessments, friction, lubrication, and wear in advanced manufacturing. Chapters cover such topics as ionic liquids, non-textured and textured surfaces, green tribology, lubricants, tribolayers, and simulation of wear.